2017
DOI: 10.1002/prp2.325
|View full text |Cite
|
Sign up to set email alerts
|

Folding correction of ABC‐transporter ABCB1 by pharmacological chaperones: a mechanistic concept

Abstract: Point mutations of ATP‐binding cassette (ABC) proteins are a common cause of human diseases. Available crystal structures indicate a similarity in the architecture of several members of this protein family. Their molecular architecture makes these proteins vulnerable to mutation, when critical structural elements are affected. The latter preferentially involve the two transmembrane domain (TMD)/nucleotide‐binding domain (NBD) interfaces (transmission interfaces), formation of which requires engagement of coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In full transporters (commonly appreciated to have arisen from half transporters by gene duplication) (Chen et al, 1986), the two halves have diverged in the course of evolution, but nevertheless have retained similarity. Our group previously demonstrated that the paradigmatic ABCB transporter P-gp (ABCB1) can bind substrates such as rhodamine 123, verapamil, vinblastine, and propafenones in dual pseudosymmetric mode (Parveen et al, 2011;Dönmez Cakil et al, 2014;Spork et al, 2017). As P-gp has two canonical NBSs, the possibility exists that substrate-binding modes and NBSs function in dedicated manner.…”
Section: Introductionmentioning
confidence: 99%
“…In full transporters (commonly appreciated to have arisen from half transporters by gene duplication) (Chen et al, 1986), the two halves have diverged in the course of evolution, but nevertheless have retained similarity. Our group previously demonstrated that the paradigmatic ABCB transporter P-gp (ABCB1) can bind substrates such as rhodamine 123, verapamil, vinblastine, and propafenones in dual pseudosymmetric mode (Parveen et al, 2011;Dönmez Cakil et al, 2014;Spork et al, 2017). As P-gp has two canonical NBSs, the possibility exists that substrate-binding modes and NBSs function in dedicated manner.…”
Section: Introductionmentioning
confidence: 99%
“…Available high-resolution structures and biochemical evidence indicate that alpha helices of the two TMDs interact to form substrate translocation conduits for the transport of cargo molecules (Dawson & Locher, 2006;Dönmez Cakil et al, 2014;Nosol et al, 2020;Parveen et al, 2011;Spork et al, 2017). Two nucleotide binding sites (NBSs) are formed at the interface of the NBDs.…”
Section: Introductionmentioning
confidence: 99%
“…A functional ATP‐binding cassette (ABC) transporter contains at least four domains: two are spanning the membrane and are therefore called transmembrane domains (TMDs), while the other two are known as the nucleotide‐binding domains (NBDs). Available high‐resolution structures and biochemical evidence indicate that alpha helices of the two TMDs interact to form substrate translocation conduits for the transport of cargo molecules (Dawson & Locher, 2006; Dönmez Cakil et al, 2014; Nosol et al, 2020; Parveen et al, 2011; Spork et al, 2017). Two nucleotide binding sites (NBSs) are formed at the interface of the NBDs.…”
Section: Introductionmentioning
confidence: 99%